Fresh versus Frozen Embryo Transfer in PCOS: Arguments for and Against - Wei, Daimin; Ma, Jinlong; Chen, Zi-Jiang (Seminars in Reproductive Medicine, 2017)
In vitro fertilization (IVF) is a common infertility treatment for women with polycystic ovarian syndrome (PCOS) who have failed to conceive in ovulation induction and who have other concomitant infertility factors. Women with PCOS tend to have an excess response to ovarian stimulation during IVF. Freeze-all strategy with deferred frozen embryo transfer was initially used to prevent ovarian hyperstimulation syndrome (OHSS) in patients with a high risk. New evidence from randomized trials showed elective frozen embryo transfer in PCOS women with a low risk of OHSS could also lower the incidence of OHSS, improve live birth rate mainly by decreasing pregnancy loss, and increase birth weight of singleton infants compared with fresh embryo transfer. However, the risk of preeclampsia was higher after frozen than fresh embryo transfer. Observational studies and limited randomized trials showed the risks of other obstetric outcomes and long-term safety profile after frozen embryo transfers were at least as good as that after fresh embryo transfer. Summarily, current evidence showed elective freeze-all and frozen embryo transfer is generally superior to fresh embryo transfer to achieve live birth in women with PCOS; however, its effect on obstetric outcome and long-term outcome warrants further studies.
Keywords: frozen embryo transfer; polycystic ovary syndrome; live birth; preeclampsia